Evaluation of natural radionuclides in Brazilian underground mines. (November 2015) - Santos, T.O.; Rocha, Z.; Vasconcelos, V.; Lara, E.G.; Palmieri, H.E.L.; Cruz, P.; Gouvea, V.A.; Siqueira, J.B.; Oliveira, A.H.
Abstract: Mineral processing releases long and short half-life radionuclides generating potential exposure to miners. They are internally exposed to radon, thoron and their short-life decay products and, externally, to the gamma emitters scattered in the rock and dust of the mine. Concerning to radiological hazards to workers, this paper focuses on the characterization of the natural radioactivity in the Brazilian underground mines. The radon and its progeny concentrations were measured by using AlphaGUARD and DOSEman detectors, respectively. Radon concentration measurement in groundwater was performed by using RAD7 detector. The 238 U and 232 Th activity concentration in ore and soil samples were determined by ICPMS. Gamma spectrometry was used to determined 226 Ra, 228 Ra and 40 K activity concentrations. The average radon concentration ranged from 113 to 4964 Bq m −3 and the average Equilibrium Equivalent Concentration varied from 76 to 1174 Bq m −3 . Based on these data, the total annual effective dose for the miners was estimated. The results suggest the need of establishing monitoring and control procedures in some mines. Highlights: The average radon concentration in each mine ranged from 113 to 4964 Bq m −3 . The average Equilibrium Equivalent Concentration ranged from 76 to 1174 Bq m −3 . The results suggest the need of establishing monitoring and control procedures in some mines.